Whole-body vibration training improves muscle mass and strength in older adults through intra- and extra-muscular pathways - Tian, Xiangyang; Fu, Shaoting; He, Jing; Ma, Rui; Shi, Rengfei (Frontiers in Cell and Developmental Biology, 2025)
Sarcopenia, a geriatric syndrome characterized by the age-related loss of muscle mass and function, is increasingly recognized to be a dynamic process and exists bidirectional transitions with both possible worsening or improving transitions. With the rapid growth of aging population, developing effective interventions to delay or prevent the progression of sarcopenia is important and urgent. Recently, growing evidence demonstrated that whole body vibration training (WBVT) could significantly improve muscle mass and/or muscle strength in older adults, and may be a promising approach for elderly adults to treat sarcopenia, but there still exists inconsistent results. To clarify the moderating variables affecting the effectiveness of WBVT on muscle mass and strength, we conducted a comprehensively search of electronic database (PubMed, Web of Science and Embase) and performed subgroup analysis depending on the characteristics of subjects (sarcopenia vs. non-sarcopenia), frequency and amplitude (low frequency low amplitude, low frequency high amplitude, high frequency low frequency and high frequency high amplitude) and body position. We found that WBVT significantly enhanced muscle strength in older adults with or without sarcopenia, and the improvements on muscle strength were greatest after WBVT intervention with high frequency high amplitude, compared with WBVT with low frequency low amplitude, low frequency high amplitude, high frequency low frequency; WBVT only increased muscle mass in non-sarcopenic individuals, body position may be an important factor influencing the effectiveness of WBVT, compared with static body position, dynamic body position during WBVT has beneficial effects on muscle mass in older adults. Furthermore, skeletal muscle contraction is under the control of motor neuron and consumes a large amount of oxygen. The factors from intra-muscular including the protein synthesis and degradation and the proliferation and differentiation of satellite cells, to extra-muscular such as microcirculation and motor neuron control are all crucial for the maintenance of muscle mass and strength, therefore, we reviewed the regulatory effects of WBVT on these indicators, which would deepen our understandings about the mechanisms about the effects of WBVT on muscle mass and strength.